Kajian hubungkait harga rumah dengan faktor kemudahan awam menggunakan sistem maklumat geografi (GIS) - Abdul Jalil, Nursyuhadah (2009)
House price could be affected by many factors. This research is conducted to relate the house price and the public facilities surround the house due to the distance between them. The establishment of the facilities and their distances to the houses affects the price of the house in certain area. Geographic Information System (GIS) provides the complete and effective tools as an integrated research framework to investigate the relationship between public facilities and housing prices. The combination of GIS and the Multicriteria Analysis (MCA) can improved the effectiveness of the housing valuation process. This research is divided into two parts. First part of this research covers the analysis of spatial pattern of the housing prices using Moran’ I. While, in the second part, spatial analyst technique were used to analyze the relationship of the housing prices and their surrounding public facilities. This study found that the spatial pattern of housing prices are random where the Moran’s I is -0.02. Spatial analyst technique shows that the house price and the public facilities are correlated. The average of housing price in area of less facilities are RM173,833.30. While, the average of housing price in area of medium facilities are RM195,134.40 and the average of housing prices in area of high facilities are RM209,278.60. In conclusion, the facilities surrounding the houses tend to influence the value of the houses. This research provides the valuable information and technique for the planner and the local authorities in process to locate public facilities.